Numerical simulation of beam propagation in a layer filled with chiral nematic liquid crystals - Sala, Filip A.; Karpierz, Mirosław A. (Photonics Letters of Poland, 2009)
Simulation of light beam propagation in chiral nematic liquid crystals, which are anisotropic media, requires the use of full-vector methods. One of them is FV-BPM (Full-Vector Beam Propagation Method). In the present work an application of FV-BPM to simulate light propagation, in the linear case, is shown. Calculations are carried out for various values of incident beam full width at half maximum, position of the launched beam and the pitch of the cholesteric. Full Text: PDF References: G. D. Ziogos, E. E. Kriezis, "Modeling light propagation in liquid crystal devices with a 3-D full-vector finite-element beam propagation method", Opt. Quant. Electron 40, 10 (2008)[CrossRef] I-C Khoo Liquid crystals John Wiley & Sons, Inc (2007) U. A. Laudyn, M. Kwasny, M. A. Karpierz, "Nematicons in chiral nematic liquid crtystals", Appl. Phys. Lett. 94, 091110 (2009)[CrossRef] U. A. Laudyn, M. Kwaśny, K. Jaworowicz, K. A. Rutkowska, M. A. Karpierz, G. Assanto, "Nematicons in twisted liquid crystals", Phot. Lett. Poland, 1, 7-9 (2009) G. Assanto, M. Karpierz, "Nematicons: self-localized beams in nematic liquid crystals", Liquid Crystals (2009) G. Assanto, M. Peccianti, C. Conti, "Optical spatial solitons in nematic liquid crystals", Opt. Photon. News 14, 44, (2003)[CrossRef] J. P Berenger, "A perfectly matched layer for the absorption of electromagnetic waves", J. Comp. Phys. 114, (1994)[CrossRef] D. S Katz, E.T. Thiele, A. "Taflove Validation and extension to three dimensions of the Berenger PML absorbing boundary condition for FD-TD meshes", IEEE Microwave Guided Wave Lett. 4, (1994) J. Baran, Z. Raszewski, R. Dąbrowski, J. Kędzierski and J. Rutkowska, "Some Physical Properties of Mesogenic 4-(trans-4'-n-Alkylcyclohexyl) Isothiocyanatobenzenes ", Mol. Cyst. Liq. Cyst. 123 (1985)[CrossRef] R. Dabrowski, J. Dziaduszek and T. Szczuciński, "Mesomorphic Characteristics of Some New Homologous Series with the Isothiocyanato Terminal Group", Mol. Cyst. Liq. Cyst. 124, 241 (1985) [CrossRef] http://physics.nist.gov/cgi-bin/cuu/Value?eqz0